Registros más occidentales de Gonatodes albogularis fuscus (Squamata: Sphaerodactylidae) en Honduras y comentarios sobre su taxonomía y conservación - Cristopher A. Antúnez-Fonseca; Oscar R. Suazo-Ortega; Alejandro J. Salguero-Sánchez; Marcio Martínez (Graellsia)
Gonatodes albogularis fuscus (Hallowell, 1855) is known mainly from the lowlands from Chiapas in Mexico to western Venezuela and Colombia and in several Caribbean islands. In Honduras it has been reported from the center, south, east and north, however there are no reports from the west of the country. We document this species for the first time in the departments of Comayagua and Intibucá in the center-west and comment on its distribution in Honduras. In addition, we suggest the need to reassess the taxonomy of subspecies of G. albogularis and comment about conservation problems derived from competition and predation by feral and invasive species and habitat modification.